(untitled) (Gaceta Técnica, 2022)
In 2019, Barquisimeto produced approximately 21,147tn of solid waste monthly, 61.79% was registered in the landfill; 33.25% ended up in streets, informal dumps, rivers and streams, and only 4.97% was processed by private recycling companies. Under this scenario, new informal jobs were generated, registering up to more than 500 street waste collectors who provided urban solid waste (USW) to companies for processing, demarcating the social segregation of the city. Through this work, a new business model is proposed, with an urban and architectural intervention, for the comprehensive management of MSW. This infrastructure was configured through a Revitalization and Adaptation Plan for inoperative spaces or those in physical-urban conflict, with different scales of intervention. It was designed based on Plazos. In the first, collection devices were configured in highly polluted areas, through participatory design and cooperatives, achieving a generic model with adaptability; whose main task is to receive USW that can generate direct economic resources for the communities. In the second, after establishing and disseminating the system as a lucrative job, the network of devices is expanded and factories are included, creating specialized spaces for the treatment of USW in industrial areas and outskirts of the city. In the third term, the core of the system is projected, revitalizing and recycling a disused building; an interpretation center whose main function is to promote an environment for learning and training informal reclaimers